Peningkatan Kreativitas Siswa Membuat Benda Konstruksi dengan Pendekatan Konstruktivisme di Kelas IV Sekolah Dasar - Harni , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The background of this research by making the learning process during the construction of objects is very far from what is expected, where the teacher is not able to present the learning that can promote the involvement of students actively and creatively in the learning process. This causes lower student creativity. The purpose of this study was to describe the increase in kretivitas students create object construction with constructivism approach grade 4 elementary school. Conducted research is classroom action research that consists of 4 stages step, namely; planning, implementation, observation, and reflection. Data was collected using observation sheet, and field notes and analyzed using qualitative and quantitative data analysis. The results showed that the constructivism approach proved effective in increasing the creativity of students in grade 4 elementary school. It can be seen from the increase in students' creativity in making the construction of objects generated at each meeting in each cycle. Increase students' creativity in making objects construction impact on increasing the value of the process and the work he made.